URGENSI MEMPELAJARI SOSIOLOGI PENDIDIKAN BAGI GURU - Utami Milyarta Lestari; Tri Adha Mayangsari; Lidia Purnama (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
ABSTRACTThis research aims to describe the importance for teachers of studying thesociology of education. This is because in the educational socialization processthere can be obstacles due to difficulties in communication and the existence ofdifferent or conflicting behavior patterns between teachers and students. Thisresearch uses descriptive qualitative methods and obtains data through literaturestudy. The results of this research are that each individual must try to harmonizeenvironmental needs and conditions as closely as possible, including at school. Therefore, it is very important for teachers to study, master and understand educational sociology because it is a science that studies the process of socialinteraction and a person's socio-cultural conditions. . Humans are socialcreatures, and everyone certainly needs other people's roles in their lives. Theserelationships and bonds are established through social interaction. In education,social interaction is studied in a science called educational sociology.